The Incidence of Continuous Training on the Effectiveness and Strengthening of Teaching Practices in the Second Cycle of Primary Level (Journal SCIENCEVOLUTION, 2025)
This study analyzes the impact of continuous training on strengthening teaching practices at the primary level in the Dominican Republic. An integrative review of 38 bibliographic sources was conducted, including academic literature, institutional documents, and empirical studies, examining the contributions, limitations, and challenges of pedagogical updating programs. The findings demonstrate that continuous training constitutes a strategic axis for teacher professional development, as it directly influences the acquisition of pedagogical, digital, and socioemotional competencies necessary to meet the demands of a globalized and technology-mediated society. Likewise, its impact on motivation, professional identity, and learning quality is acknowledged, although limitations persist, such as the lack of articulation with initial training, the absence of institutional follow-up, and digital divides, especially in rural contexts. Successful experiences in pedagogical mentoring, specialization in disciplinary areas, and the use of technological resources were also highlighted, although these practices require greater sustainability and contextual relevance. In conclusion, the need for comprehensive educational policies that promote situated, collaborative, and reflective continuous training is proposed, capable of ensuring equitable and quality education, thereby consolidating teachers as key agents of innovation and social transformation.
Keywords: Continuous Professional Development; Teaching Practice; Digital Competencies; Educational Quality; Pedagogical Innovation; Primary Education; Teacher Professionalization